Caluera qorillaryana, a new orchid species and first record of the genus for the Peruvian flora - Calatayud Hermoza, Gloria (2021)
A new species, Caluera qorillaryana (Oncidiinae, Orchidaceae) from southern Peru is described and illustrated, with comments on its ecology, geographical distribution, and conservation status. The new species, inhabith in Andean-Amazonian foothill forest in the Pongo de Qoñec, Kosñipata valley, is the five species of Caluera to be described and also represents the first record of the orchid genus for the flora of Peru.